PAIN, ANGER AND HOPE IN PRIMA FACIE: POLITICISING THE CONTEMPORARY SUBJECT THROUGH AFFECTIVE DEPICTIONS OF RAPE ON STAGE - Mac Eochagain, Bridget (Australasian drama studies, 2025)
From a feminist viewpoint, Elaine Aston articulates why the 'dangers' of the contemporary world - whether it be violence, injustice or political responses to culture - are frequently engaged with in theatre practice, as '[t]heatre has the political power to stage the world that is and to invite us to see the other worlds that might be'.· Feminist scholar Davida Bloom considers this concern in feminist discourse on rape's prevalence in contemporary theatre culture, where '[p]lays about rape produce meanings that extend far beyond an engaging afternoon reading a script or an evening at the theatre as they contribute to the readers' or audience members' impressions of rape and raped women'.· Alongside rape's long-standing place in theatre is a contemporary counter-narrative that is resisting the performance of rape for its own sake, considering rather its dramaturgical purpose; that is, why do we perform rape? Rachel Fensham explores this concern in her 2016 chapter on 'affective spectatorship", where she states: "[T] heatre and performance studies have been taking the spectator and the audience seriously; the questions are no longer what stimulates individual spectators to act but how they feel, and whether audience participation has been affective or not?" This has arguably been leading feminist discourses in the wake of the #MeToo movement, where ideas of trauma-informed and consent-based practices have dominated performance industries, contributing to the 'affective turn" · The cultural impact of this turn has led to wider collective understandings of affective feelings as a tool for revealing 'critical links between affect and gendered, sexualized, racialized and classed relations of power'.' By framing one through the other, contemporary performances of sexual violence and harm are arguably able to use these tools to fracture the structures of power which oppress victims. [...]Ahmed's theory on the cultural politics of affective feeling is a powerful mode for reframing sexual violence and harm on stage. Ultimately, emotions have been framed as oppressive to the feminine subject, and as Ahmed argues, this requires that we (re) frame or (re)orientate emotions and affect through a feminist lens. [...]the 'feminisation' of emotion has arguably contributed to the gendered criticism of feminist thought in contemporary Western culture, where '[fJeminists who speak out against established "truths" are often constructed as emotional, as failing the very standards of reason and impartiality that are assumed to form the basis of "good judgement™.·? Orchestrating social perceptions of feminism as "less than' reifies how structures of power have managed to suppress and dismiss feminist advocacy.